2017
DOI: 10.2298/tsci160218082v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the shape of soaring particle based on coal-water slurry containing petrochemicals on ignition characteristics

Abstract: This paper examines the laws of stable ignition of organic coal-water slurry containing petrochemicals (CWSP). The CWSP is based on the filter cake of coal and scavenge oil. The experiments are performed for individual CWSP particles soaring in a special setup. The temperature and velocity of an oxidizer flow are varied between 500-1200 K, and 0.5-3 m/s. The dimensions (longitudinal and transverse) of particles range are from 0.5 mm to 5 mm. The study indicates how the shape of a fuel particle (sphere, ellipso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In particular, the database of reliable kinetic constants is expanded, which is based on a set of papers published over the last 20 years, e. g. we can underline works [34][35][36][37][38]. The development of laboratory-based measurement equipment will help us take major steps to create a unified database of thermophysical and thermokinetic characteristics of widely used solid and composite fuels [39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the database of reliable kinetic constants is expanded, which is based on a set of papers published over the last 20 years, e. g. we can underline works [34][35][36][37][38]. The development of laboratory-based measurement equipment will help us take major steps to create a unified database of thermophysical and thermokinetic characteristics of widely used solid and composite fuels [39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the features and limitations identified above, it is advisable to develop an experimental method that ensures a soar of particle (for a single one, small group and a flow of CLF particles) of the fuel composition in a flow of heated air with the ability to control its ignition and combustion processes (using high-speed video recording). The results of studies using a specialized model combustion chamber can be found in [16,17]. It is shown that the conditions of the experiments [16,17] correspond closely to furnaces of thermal power plants, boiler houses, and other power plants, as the fuel particles in them soar after injection into the combustion chamber by the nozzle.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, to determine differences between the integral characteristics, the experiments were held with different shapes of droplets (sphere, ellipsoid and polyhedron). It has been found that the polyhedron droplets are characterized by minimal ignition delay time, which is associated with an increased contact area due to numerous ledges [28].…”
Section: Differences In the Characteristics Of Ignition Of Slurry Fuementioning
confidence: 99%